Status of Abortion-Related Stigma in Nepal using Stigmatizing Attitudes, Beliefs, and Actions Scale - Ghimire, Jagadishwor; Lal, Bibek Kumar; Mehata, Suresh; Joshi, Nisha Kumari; Timilsina, Amit; Lamichhane, Kritee; Phuyal, Parash Prasad; Dotel, Bhogendra Raj; Gautam, Manish; Maharjan, Sanju; Karki, Sujan (Journal of Nepal Health Research Council, 2024)
Background: Despite substantial improvements in the accessibility of safe abortion services nationwide, a noticeable underutilization of these services persists, primarily attributable to the presence of social stigma. This stigma leads to discrimination, abuse, and poor healthcare. This study aims to understand and address abortion stigma among Nepali women of reproductive age.Methods: This cross-sectional study involved 2286 women of reproductive age across Nepal. SABAS was used to measure abortion stigma, which includes 18 questions. Quantitative data was collected through face-to-face interviews using structured questionnaires on kobo collect. Stata 15.0 software was used for data analysis.Results: The mean SABAS score was 46.5 out of 90, indicating moderate abortion stigma in Nepal. Negative stereotypes and beliefs about abortion were more prevalent, with over 80% believing a woman's health deteriorates after abortion. Discrimination tendencies were lower, with less than 10% endorsing teasing, pointing fingers, or disgrace. Fear of contagion was also relatively low, with less than 20% agreeing that women who had abortions made others ill. Factors such as age, caste/ethnicity, education, marital status, wealth, and provinces were associated with varying levels of stigma, and women of higher age group, Madhesh, Dalit, Muslim, lower education levels, widowed, poor, Madhes province were linked to higher stigma scores. The study found that stigma levels varied among different groups.Conclusions: The stigma level on abortion is higher in upper age group, Madheshi, Dalit, Muslim, lower education levels, widowed, poor, Madhesh province women in Nepal. Similarly, the negative stereotype and discrimination and exclusion is also high while the fear of contagion is low among Nepalese women and girls.Keywords: Abortion-related stigma; attitudes; Nepal.